Pendidikan Islam sebagai Ekosistem Adaptif-Transformatif: Menavigasi Perubahan Sosial Budaya di Era Society 5.0 - Fani Rahmasari; Andi Aris (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the nature of Islamic education as an adaptive-transformative ecosystem in facing the dynamics of contemporary socio-cultural change. This study uses a qualitative approach with library research sourced from books, journal articles, and relevant scientific literature, and analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results show that Islamic education has transformed into an organic ecosystem that acts as an ethical navigator (vanguard of humanity) in guiding the direction of civilization. Through the reconstruction of the concept of Insan Kamil, Islamic education is able to integrate science and religion holistically, thus giving birth to digital piety and contributing to mitigating the cultural gap (culture lag). In addition, Islamic education also plays a significant role in building spiritual resilience to face the mental health crisis and the phenomenon of self-alienation in the Alpha generation. The conclusion of this study confirms that Islamic education as an adaptive-transformative ecosystem is a strategic solution in responding to the global existential crisis, while also being the foundation for building a moderate, balanced, and just civilization based on the principle of rahmah li al-‘ālamīn. This research is limited by its theoretical-conceptual focus, requiring further empirical validation to test its effectiveness in the field. Therefore, it is recommended to develop a digital literacy-based curriculum integrated with character building and equitable infrastructure support for Islamic educational institutions